Effect of red and infrared low-level laser therapy in endodontic sealer on subcutaneous tissue - Sivieri-Araujo, G. [UNESP]; Berbert, Fabio Luiz Camargo Villela [UNESP]; Ramalho, L. T. O. [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Crisci, F. S. [UNESP]; Bonetti-Filho, I. [UNESP]; Tanomaru-Filho, M. [UNESP] (Maik Nauka/interperiodica/springer, 2011)
This study evaluated the reactions of connective tissue after the implant of one endodontic sealer (Endofill) that was irradiated with low-level laser therapy (LLLT). Sixty mice were distributed into three Groups (n = 20): GI-the tubes filled with Endofill were implanted in the animals and were not irradiated with LLLT; GII-the tubes containing Endofill were implanted in the animals and then irradiated with red LLLT (InGaAlP, lambda = 685 nm, P = 35 mW, t = 58 s, D = 72 J/cm(2), E = 2 J, = 0.60 mm, continuous mode) and GIII-the tubes with Endofill were implanted and irradiated with infrared LLLT (AsGaAl, lambda = 830 nm, P = 50 mW, t = 40 s, D = 70 J/cm(2), E = 2 J, = 0.60 mm, continuous wave) both are semiconductor diode laser device. The animals were killed after 7 and 30 days. Series sections of 6 mu m thickness were obtained and stained with Hematoxylin-Eosin and Masson Trichrome. The data of the histopathological evaluation were submitted to Kruskal-Wallis and Dunn's tests at 5% significance level. At the 7th day: GI showed the presence of inflammation; GII and GIII reduced inflammation. At 30th day: GI showed low inflammation; GII and GII the absence of inflammation. It was possible show that LLLT reduced the irritating effect promoted by the Endofill, in the period of 7 days (p > 0.05). The tissue repair occurred in 30 days, regardless of the use of LLLT.